2010
DOI: 10.5012/bkcs.2010.31.5.1377
|View full text |Cite
|
Sign up to set email alerts
|

Determination of a Binding Site of Cu, Ni, Mg, and Ca Metal Ions with Angiotensin II Peptide by Electrospray Tandem Mass Spectrometry

Abstract: Angiotensin II (Ang II) is the main active hormone in the renin-angiotensin blood pressure regulation system. 1 Ang II is an octapeptide hormone (Asp1-Arg2-Val3-Tyr4-Ile5-His6-Pro7-Phe8, DRVYIHPF) that has been studied for several decades in the structure-dependent activity of the biological pathway of the Ang II receptor. [2][3][4][5][6][7][8][9][10][11][12][13] Free Ang II molecular structures in solutions have been investigated with a variety of techniques. The results have been reported as β-turn, random c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…In Figure a, the peaks of Ang I monocoordinated copper(II) are observed, demonstrating the presence of Ang I–Cu 2+ during the Ang I nitration. According to the tandem MS results shown in Supporting Information S-9, Cu 2+ should bind to the carbonyl group on the backbone between valine and tyrosine, in accordance with the literature . The structure of Ang I–Cu 2+ is shown in Scheme .…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In Figure a, the peaks of Ang I monocoordinated copper(II) are observed, demonstrating the presence of Ang I–Cu 2+ during the Ang I nitration. According to the tandem MS results shown in Supporting Information S-9, Cu 2+ should bind to the carbonyl group on the backbone between valine and tyrosine, in accordance with the literature . The structure of Ang I–Cu 2+ is shown in Scheme .…”
Section: Resultssupporting
confidence: 82%
“…According to the tandem MS results shown in Supporting Information S-9, Cu 2+ should bind to the carbonyl group on the backbone between valine and tyrosine, in accordance with the literature. 60 The structure of Ang IÀCu 2+ is shown in Scheme 3. Because it has been reported that amino acid monocoordinated Cu 2+ shows enhanced activity for the decomposition of H 2 O 2 , 61 it can be proposed that both peptidecoordinated and noncoordinated Cu 2+ may play a role in the copper-catalyzed tyrosine nitration.…”
mentioning
confidence: 99%
“…According to our previous studies, 20 copper(II) can be coordinated by Ang I and the binding happens close to the tyrosine residue of Ang I. The same binding site between Ang I and copper(II) was also reported by Kim et al 35 In Fig. 1(a), the copper coordinated Ang I is observed as a small peak after the nitrated Ang I ((Ang I + NO 2 ) 3+ ).…”
Section: Tyrosine Nitration Influenced By Reactant Concentrationssupporting
confidence: 81%